Advances in industrial and labor relations. Vol. 16 - Lewin, David, 1943-; Kaufman, Bruce E. (Advances in industrial and labor relations., 2009)
Volume 16 of Advances in Industrial and Labor Relations (AILR) highlights important and interesting aspects of industrial and labor relations. Such issues include alternative approaches to establishing an ownership culture, accounting for union collective action through resource acquisition and mobilization, union avoidance through double-breasting, labor-management partnership and mutual gains, high involvement work systems and union-management communication networks, a new paradigm for IR/HR theory and research, implications for women of private pension reform, and competing ethical conceptions of the minimum wage.